EVALUATING THE WORK DESIGN READINESS FOR INDUSTRY 4.0 BASED ON PERSONAL CHARACTERISTICS OF PRODUCTION WORKERS: Work Design Readiness for Industry 4.0 - Abubakar Bugvi, Salman; Mughal, Khurram Hameed; Jamil, Muhammad Fawad; Kazim, Ali Hussain; Shabbir, Aqsa; Shahid, Muhammad Usama; Dar, Muhammad Uzair; Asif, Muhammad Musa; Imran, Hassan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The design of work is a crucial consideration for production workers in terms of performance, satisfaction, and motivation. This aspect has garnered increasing attention in research, particularly with the rise of automation and the transition to Industry 4.0-enabled smart factories. Work design is influenced by both internal and external performance-shaping factors (PSFs). Internal factors include human, machine and task elements and traits, which HR specialists can structure to enhance efficiency and productivity in manufacturing. External PSFs, such as physical, psychological, social and organizational factors, also play a significant role in shaping production work. This study aims to understand the impact of personal characteristics of production workers in an automated factory. The research findings are extrapolated on an Industry 4.0 framework to establish a productive work design. Data collection is conducted through a quantitative survey, and non-parametric analysis of variance tests are employed to assess significant relationships. The results indicate a better perception of the pace of operations (µ = 4.19) and feedback (µ = 4.47) among elder workers. Additionally, educated workers express significant perceptions regarding external PSFs such as supervision (µ = 4.39), health and safety (µ = 4.25), job rotation (µ = 3.91) and pay and welfare (µ = 3.58). Aspiration, motivation and organizational commitment emerge as crucial work design attributes for experienced and married workers. These findings contribute to understanding the structure of modern work design in the context of Industry 4.0, aiming to enhance performance and worker productivity. The study proposes an advanced Industry 4.0 work design framework, empowering HR specialists to develop effective strategies and optimize work distribution.